Planetary systems in the universe observation, formation and evolution: proceedings of the 202nd Symposium of the International Astronomical Union held ... Manchester, ... August 7-10, 2000 - Penny, Alan (Proceedings of the ... symposium of the International Astronomical Union, 2004)
Discovery and study of extrasolar planets: current -- Progress in the theory of planet formation -- Structure and atmosphere of planets -- Protoplanetary and beta Pic disks -- Discovery and study of extrasolar planets: future
Keywords: Konferenzschrift; Planetensystem